2021
DOI: 10.3390/ijms23010041
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of pH, Temperature, and Surfactant Structure on Bovine Serum Albumin–Cationic/Anionic/Nonionic Surfactants Interactions in Cacodylate Buffer–Fluorescence Quenching Studies Supported by UV Spectrophotometry and CD Spectroscopy

Abstract: Due to the fact that surfactant molecules are known to alter the structure (and consequently the function) of a protein, protein–surfactant interactions are very important in the biological, pharmaceutical, and cosmetic industries. Although there are numerous studies on the interactions of albumins with surfactants, the investigations are often performed at fixed environmental conditions and limited to separate surface-active agents and consequently do not present an appropriate comparison between their differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 95 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The biological activity of the proteins is highly impacted by their secondary structure [ 56 , 57 ]. Some operational conditions such as a harsh temperature or a pH change or the presence of specific chemicals may cause conformational changes as well as protein unfolding and, consequently, the loss of activity [ 58 , 59 , 60 ]. Several studies reported trypsin conformational changes in the presence of environmental conditions such as the presence of salts, various solvents, and temperature [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of the proteins is highly impacted by their secondary structure [ 56 , 57 ]. Some operational conditions such as a harsh temperature or a pH change or the presence of specific chemicals may cause conformational changes as well as protein unfolding and, consequently, the loss of activity [ 58 , 59 , 60 ]. Several studies reported trypsin conformational changes in the presence of environmental conditions such as the presence of salts, various solvents, and temperature [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…15,16,18 A strong dependence of the interaction between the two components on temperature has also been reported, where binding energy, critical aggregation concentration and other thermodynamical parameters have been shown to be influenced by temperature variation. 20–22 However, in most cases, the temperature range studied remains close to room temperature, where neither the protein, nor the surfactant, nor their complexes undergo significant macroscopic changes. 2,16,20–22 Temperature is a critical parameter for influencing protein–surfactant interactions as it is known to affect protein conformation and drives morphological transitions in surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…20–22 However, in most cases, the temperature range studied remains close to room temperature, where neither the protein, nor the surfactant, nor their complexes undergo significant macroscopic changes. 2,16,20–22 Temperature is a critical parameter for influencing protein–surfactant interactions as it is known to affect protein conformation and drives morphological transitions in surfactants. 23–29 When subjected to high temperatures, proteins undergo unfolding.…”
Section: Introductionmentioning
confidence: 99%